Assessing the differences between uncomplicated and complicated acute appendicitis: From accurate diagnosis to tailored treatment - Sula, Sami (fi=Turun yliopisto|en=University of Turku|, 2025)
Acute appendicitis is one of the most common reasons for acute abdomen. Current epidemiological and clinical studies clearly suggest that appendicitis consists of a diverse spectrum of variable disease severity forms. This results in multiple treatment alternatives as uncomplicated acute appendicitis can be treated with antibiotics and even with only symptomatic treatment, while complicated appendicitis mainly requires emergency operation. Appendicitis can be broadly divided into uncomplicated and complicated appendicitis often distinguished using CT imaging. The knowledge gap is the accurate differential diagnosis with uniform definitions of appendicitis severity especially in the middle ground ”grey area” between these two disease forms. Accurate differential diagnosis allows optimization of all treatment options for both patients and healthcare systems. The main aim of this thesis was to assess the differences in blood-culture positivity rate between uncomplicated and complicated acute appendicitis and to improve the accuracy of CT imaging in differential diagnostics between the different disease severities. In addition, the longer-term outcomes of antibiotic and symptomatic treatment for uncomplicated acute appendicitis were assessed. Study I investigated blood culture positivity in patients with acute appendicitis. Studies II and III evaluated CT imaging findings to better identify and rule out complicated acute appendicitis using a large prospective patient cohort. Study II assessed the association of appendicolith CT characteristics with appendicitis severity and study III aimed to identify potential prognostic CT factors for complicated appendicitis. Study IV was a 3-year follow-up of the APPAC III randomized double-blind clinical pilot trial comparing antibiotics to placebo in adults with CT-confirmed uncomplicated appendicitis. Complicated appendicitis was associated with higher rates of bacteremia compared to uncomplicated appendicitis, and the overall prevalence of blood culture positivity in patients with acute appendicitis was 9%. The presence of appendicolith in patients with acute appendicitis increased the risk of complicated appendicitis. CT findings associated with complicated acute appendicitis included larger appendiceal diameter, appendiceal wall enhancement defect and accumulation of fluid around the appendix. At 3 years, there was no difference between antibiotics and placebo in terms of treatment success with an overall appendectomy rate of 35%.

Komplisoituneen ja komplisoitumattoman umpilisäketulehduksen erojen arviointi Akuutti umpilisäketulehdus eli appendisiitti on yleisin akuutin vatsan syy. Uusimpien epidemiologisten ja kliinisten tutkimuksien mukaan umpilisäketulehdus koostuu vaikeusasteeltaan vaihtelevien erilaisten tautimuotojen kirjosta. Tämä on johtanut useisiin eri hoitomahdollisuuksiin, kuten komplisoitumattoman umpilisäketulehduksen hoitoon antibiooteilla tai jopa oireenmukaiseen hoitoon, mutta komplisoitunut umpilisäketulehdus useimmiten vaatii edelleen kiireellisen päivystysleikkauksen. Umpilisäketulehdus voidaan jakaa pääpiirteittäin komplisoitumattomaan ja komplisoituneeseen muotoon, jotka ovat erotettavissa toisistaan tietokonetomografiakuvauksen (TT) avulla. Umpilisäketulehduksen vaikeusasteiden erotusdiagnostiikan ongelma on näiden tautimuotojen väliin jäävä merkittävä harmaa alue. Tarkempi erotusdiagnostiikka mahdollistaa kaikkien eri hoitovaihtoehtojen optimoinnin, minkä avulla voidaan parantaa potilaiden saamaa hoitoa sekä sairauden ja hoidon yhteiskunnalle aiheuttamia kustannuksia. Tämän väitöskirjatyön tavoitteena oli arvioida appendisiitin erotusdiagnostiikan parantamista keskittyen veriviljelypositiivisuuteen sekä TT-löydöksiin. Lisäksi väitöstyössä arvioitiin komplisoitumattoman umpilisäketulehduksen antibiootti- ja oireenmukaisen hoidon pitkäaikaistuloksia. Osatyö I tutki veriviljelypositiivisuuden esiintymistä umpilisäketulehduksessa. Osatöissä II ja III arvioitiin komplisoituneeseen umpilisäketulehdukseen liittyviä TT-löydöksiä laajan prospektiivisen potilasmateriaalin avulla. II osatyö arvioi ulostekiven (fekoliitti) merkitystä ja osatyö III keskittyi yleisempiin TT-löydöksiin. Osatyö IV oli APPAC III satunnaistetun kaksoissokkoutetun monikeskustutkimuksen 3-vuotisseurantatutkimus, jossa verrattiin antibioottia lumelääkkeeseen komplisoitumattoman umpilisäketulehduksen hoidossa. Veriviljelypositiivisuus oli yhteydessä komplisoituneeseen tautiin ja sen esiintyvyys umpilisäketulehduksessa oli 9 %. Fekoliitti lisäsi merkittävästi komplisoituneen umpilisäketulehduksen riskiä. TT-löydöksistä umpilisäkkeen halkaisija, seinämän tehostumattomuus sekä lisääntynyt nestemäärä umpilisäkkeen ympärillä olivat yhteydessä komplisoituneeseen appendisiittiin. 3-vuotisseurannassa lumelääkkeen ja antibiootin välillä ei ollut eroa hoidon onnistumisessa ja umpilisäkkeen poisto tehtiin 35 %:lle potilaista.